(untitled) (International Journal of Engineering and Computer Science, 2015)
In this era of Globalization, the extensive use of SmartPhones in our day-to-day life has become a very important factor. According to surveys, nearly 0.8 of the SmartPhone industry is dominated by Android. Therefore, the issue of Security and Privacy of the User becomes a crucial factor to be taken care of. Since, Android is an Open-Source Platform, the scope of resolving issues like this becomes easy and effective with the help of applications designed by programmers around the globe. Smartphones running on Android OS have an in-built password detection mechanism (character/pattern/gesture) which helps in differentiating between real user from unknown user. Also, the proposed system are designed to work with their own perspective to meet the users demands and this done with the help of pre-defined sensors which are thoroughly elaborated after a lot of search. In this paper, A survey of the research done by the predecessors on related subject to provide better security and to overcome this breach of privacy. Now while discussing the security measures, The system can possibly assume that under a certain type of scenario an intruder may try to access valuable information of the user without his knowledge and when faced with a password barrier, the intruder may try to bypass it by entering another password, and if the password is wrong it may result in multiple failed attempts. So there has to be certain solution to detect this breach and if possible overcome it. Along with this, the proposed system should make sure that the application consumes least amount of battery and uses minimum amount of system memory.